The effects of natural landscape elements in combating emerging desertification in Northern Nigeria - Yahaya, Abdul Ahmed (2021)
Desertification or land degradation is a serious environmental problem with tremendous socio-economic consequences. Today's northern Nigeria arid and semi-arid zones are affected by desertification resulting from various factors, from climatic variations to anthropological activities such as bush fire, deforestation, grass-shrub, and tree thickening, degradation, over-cultivation, and overgrazing. Many policies and programs have been formulated and implemented at the national and international levels to address this phenomenon. Programs like afforestation are one of the most effective means of preventing desertification in conjunction with natural landscape elements. Consequently, with the constrained availability of human and ecological resources, there are widespread negative impacts on security. The purpose of this research was to establish the merit and demerit of desertification, to assess the causal factor, and recommend a sustainable method using Natural Landscape Elements (indigenous tree species) in combating drought and desertification, this includes variables of stocking rate, natural mortality, chopping, cutting, grafting and seedling regeneration. The effects of methods of afforestation and reforestation on the promotion of bio-diversity have been investigated. The Stratification Sampling Approach was used for this study. Primary data was compiled using structured interviews. Questionnaires were used to obtain quantitative data from 30 villages in three Local Government Councils of Kano State namely Danbatta, Gabasawa, and Tsanyawa. Secondary data relied on the internet and library research. The major findings of the study include; (i) Anthropological activities are the major determinants of climatic changes; (ii) Climatic changes have notably led to resource scarcities with fundamental effects on various aspects of anthropologic securities in the region of Northern Nigeria; (iii) Climate change served as a key driver of anthropological insecurity. It was also revealed that the government can address the process of desertification using elements for sustainable reforestation projects. It was recommended that while dealing with climate and anthropological changes, global, regional, and national institutions, regimes, and policies be guided by taking into consideration of the broader anthropologic insecurities. Finally, the therapeutic effect using Natural Landscape Elements will serve as the Gap while the Natural Elements is a novelty in the research.